Relationship of parental occupation, income, and education with children's oral health: A study of sixth-grade students at SD 060847 Sekip, Medan - Molek, Molek; Gusbakti, Gusbakti; Khairani, Nayla; Sembiring, Reza (Buletin Kedokteran & Kesehatan Prima, 2026)
Background: Oral health in elementary school–aged children is an important component of general health that affects quality of life and the growth and developmental process. Poor oral hygiene in children remains common and is influenced by various factors, including parental socioeconomic conditions. This study aimed to determine the relationship between parental socioeconomic factors, including occupation, income, and education level, and the oral health of sixth-grade students at SD Negeri 060847. Methods: This analytic survey used a cross-sectional design. The study population comprised all students at SD Negeri 060847, and the sample consisted of 43 sixth-grade students selected using a total sampling technique. Data on parental socioeconomic status were obtained through questionnaires, and children’s oral health status was assessed using the Oral Hygiene Index Simplified (OHI-S) through direct examination. Data were analyzed using univariate and bivariate methods with the chi-square test. Most children had a moderate OHI-S status. Results: There was a significant relationship between parental occupation and children’s OHI-S status, with children whose parents had higher-level occupations tending to have better oral hygiene. Parental income also showed a significant relationship with OHI-S status, with higher income associated with better oral hygiene. In addition, parental education level was significantly associated with children’s oral health. Conclusion: In conclusion, parental socioeconomic factors are significantly associated with the oral health of sixth-grade students at SD Negeri 060847.